Faktor-Faktor Yang Berhubungan Dengan Mortalitas Pasien Di Intensive Care Unit Rumah Sakit Panti Rapih Yogyakarta - Wungo, Jefry Ade; Widyastuti, Chatarina Setya; Rina Setyan, Fransisca Anjar (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
ABSTRACT Background: Mortality of ICU patients at Panti Rapih Hospital in 2020 reached 33.25%. Patient mortality can be caused by sepsis, cardiac arrest, ARDS, old age problems, comorbidities, VAP and postoperatively. Nurses have an important role in continuous monitoring. Objective: This study aims to identify factors associated with mortality in ICU patients at Panti Rapih Hospital Yogyakarta. Methods: This study is a retrospective case-control quantitative study. The research population was 424 respondents, with a research sample of 208 respondents taken randomly with quota sampling technique. Data collection with medical record observation sheets. Analysis of univariate data using percentage analysis and bivariate analysis using Chi-Square and Kolmogorov-Smirnov. Results: The results showed that there was no significant relationship between age and patient mortality with p-value 0.266, there was a significant relationship between comorbidities and patient mortality with p-value 0.040, there was a significant relationship between sepsis and patient mortality with p-value 0.001 , there is a significant relationship between CPR and patient mortality with a p-value of 0.000, there is a significant relationship between ARDS and patient mortality with a p-value of 0.035, there is a significant relationship between VAP and patient mortality with a p-value of 0.000, there is a significant relationship between surgery and patient mortality with a p-value of 0.012. Conclusion: Statistics show that there is no significant relationship between age and mortality, there is a significant relationship between comorbidities, sepsis, cardiopulmonary resuscitation, ARDS, VAP, surgery and mortality of ICU patients at Panti Rapih Hospital. The need for clear indicators and policies regarding the criteria for patients being treated and transferred from the ICU on the basis of the benefits of intensive therapy. Keywords: ICU (Intensive Care Unit), patient criteria, mortality